Nitrate Transporter Gene Expression and Kinetics of Nitrate Uptake by Populus × canadensis ‘Neva’ in Relation to Arbuscular Mycorrhizal Fungi and Nitrogen Availability - Wu, Fei; Fang, Fengru; Wu, Na; Li, Li; Tang, Ming (Frontiers in Microbiology, 2020)
Plants and other organisms in the ecosystem compete for the limited nitrogen (N) in the soil. Formation of a symbiotic relationship with arbuscular mycorrhizal fungi (AMF) may influence plant competitiveness for N. However, the effects of AMF on plant nitrate (NO3-) uptake capacity remains unknown. In this study, a pot experiment was conducted to investigate the effects of N application and Rhizophagus irregularis inoculation on the root absorbing area, uptake kinetics of NO3- and the expression of NO3- transporter (NRT) genes in Populus × canadensis ‘Neva’. The results showed that R. irregularis colonized over 70% of the roots of poplar and increased root active absorbing area/total absorbing area. The uptake kinetics of NO3- by poplar fitted the Michaelis-Menten equation. Mycorrhizal plants had a higher maximum uptake rate (Vmax) value than non-mycorrhizal plants, indicating that R. irregularis enhanced the NO3- uptake capacity of poplar. The expression of NRTs in roots, namely NRT1;2, NRT2;4B, NRT2;4C, NRT3;1A, NRT3;1B and NRT3;1C, was decreased by R. irregularis under conditions of 0 and 1 mM NH4NO3. This study demonstrated that the improved NO3- uptake capacity by R. irregularis was not achieved by up-regulating the expression of NRTs in roots. The mycorrhizal pathway might repress root direct pathway in the NO3- uptake by mycorrhizal plants.